Influence of gasoline inhalation on the enantioselective pharmacokinetics of fluoxetine in rats - Cardoso, Juciane Lauren Cavalcanti; Lanchote, Vera Lucia; Pereira, Maria Paula Marques; Capela, Jorge Manuel Vieira [UNESP]; Lepera, José Salvador [UNESP] (Wiley, 2013)
Fluoxetine is used clinically as a racemic mixture of (+)-(S) and (-)-(R) enantiomers for the treatment of depression. CYP2D6 catalyzes the metabolism of both fluoxetine enantiomers. We aimed to evaluate whether exposure to gasoline results in CYP2D inhibition. Male Wistar rats exposed to filtered air (n = 36; control group) or to 600 ppm of gasoline (n = 36) in a nose-only inhalation exposure chamber for 6 weeks (6 h/day, 5 days/week) received a single oral 10-mg/kg dose of racemic fluoxetine. Fluoxetine enantiomers in plasma samples were analyzed by a validated analytical method using LC-MS/MS. The separation of fluoxetine enantiomers was performed in a Chirobiotic V column using as the mobile phase a mixture of ethanol:ammonium acetate 15 mM. Higher plasma concentrations of the (+)-(S)-fluoxetine enantiomer were found in the control group (enantiomeric ratio AUC(+)-(S)/(-)-(R) = 1.68). In animals exposed to gasoline, we observed an increase in AUC0-∞ for both enantiomers, with a sharper increase seen for the (-)-(R)-fluoxetine enantiomer (enantiomeric ratio AUC(+)-(S)/(-)-(R) = 1.07), resulting in a loss of enantioselectivity. Exposure to gasoline was found to result in the loss of enantioselectivity of fluoxetine, with the predominant reduction occurring in the clearance of the (-)-(R)-fluoxetine enantiomer (55% vs. 30%). Chirality 25:206-210, 2013. © 2013 Wiley Periodicals, Inc. Copyright © 2013 Wiley Periodicals, Inc.
Keywords: enantiomers; fluoxetine; gasoline inhalation exposure chamber; LC-MS/MS; pharmacokinetics; alcohol; ammonium acetate; cytochrome P450 2D6; gasoline; animal experiment; animal tissue; area under the curve; controlled study; drug blood level; enantiomer; enantioselectivity; enzyme inhibition; inhalation; limit of quantitation; liquid chromatography; male; nonhuman; priority journal; racemic mixture; rat; single drug dose; tandem mass spectrometry